Aspirations and Networks of Italian Migrants to Bogota. A Typology - Angela Delli Paoli; Domenico Maddaloni (Qualitative Sociology Review)
This paper aims to understand the individual and relational motives supporting migration from Italy to Bogota. Our concern is to achieve a nuanced understanding of how aspirations, on the one hand, and social networks, on the other, shape migratory decisions and structure in broader migration patterns. To do this, we chose a qualitative approach based on narrative interviews with Italians living in Bogota, which were selected through snowball sampling. As a result, we produced a typology of five different migration pathways: globetrotters aspiring to international mobility with no mediators supporting their process of continuous migration; careerists who accept moving on demand of their company for advancing their career supported by professional mediators; risk-takers aspiring to professional independence and supported in their entrepreneurial project by weak ties; tied migrants aspiring to better family quality of life and supported by strong familial ties; and exiled migrants who find a refuge from the difficulties they encounter in Italy and supported by strong professional ties.